2024
DOI: 10.24084/repqj12.285
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Power Conditioning with Harmonic Reduction in Microgrids

Abstract: This paper presents a control method ofRenewable Energy Sources (RES) to reduce the harmonic content of the distribution system to which are connected, such as a Microgrid. By this method the RES is acting as a Power Conditioner and its supplying system consists of a buck-boost converter connected back-to-back to a polarity swapping inverter. A RES or a Distributed Generator (DG) such as a microturbine is synchronized to the distribution system, which is assumed to be distorted by a high-order voltage harmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Furthermore, methods based on selective harmonic elimination suppress harmonics caused only by the operation of the converter itself. Our method, tackles the harmonic content of the output, no matter if it is created by the converter, the source, the isolated loads or microgrid [12].…”
Section: Harmonic Reduction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, methods based on selective harmonic elimination suppress harmonics caused only by the operation of the converter itself. Our method, tackles the harmonic content of the output, no matter if it is created by the converter, the source, the isolated loads or microgrid [12].…”
Section: Harmonic Reduction Methodsmentioning
confidence: 99%
“…4624-4632], [12]. The harmonic content of the output is calculated with a fast Fourier transformation (FFT).…”
Section: Harmonic Reduction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it is suitable either for simple current harmonic reduction or as a self-healing mechanism. Having in mind [16], it can be concluded that the proposed topology can provide both voltage and current harmonic reduction in microgrids (or generally in distribution systems), depending on which kind of distortion exists. Finally, the above mentioned theory and simulation results were experimentally confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The converter configuration proposed in [15] and already used in [16] has been used in this work in order to reduce the current harmonic content of the grid, so that the Total Harmonic Distortion (THD) index is decreased to below acceptable limits. It consists of a dc/dc buck-boost converter connected to the grid through a simple polarity changing inverter.…”
Section: Introductionmentioning
confidence: 99%